Using Continuing Professional Development with Portfolio in a Pharmaceutics Course - Jennifer Schneider; Kate O'Hara; Irene Munro (MDPI AG, 2016)
The introduction of Continuing Professional Development (CPD) to encourage individual life-long learning as a way of maintaining professional competency in pharmacy has faced resistance. To investigate ways to address this barrier we included CPD with portfolio in a university Pharmaceutics course. Underpinning knowledge for the course was delivered using a flipped classroom approach and students used the CPD model to address clinical scenarios presented in a simulated pharmacy setting. Students produced portfolio items for the different case scenarios and submitted these for assessment. This provided the opportunity for students to carry out repeated application of the CPD cycle and, in so doing, develop skills in critical thinking for self-reflection and self-evaluation. This course was designed to encourage the development of higher level learning skills for future self-directed learning. Thirty six students submitted a completed portfolio. Twenty nine students achieved a result of >70%, five students scored between 57%-69%, one student obtained a mark of 50% and one student failed. The end of course survey revealed that while students found portfolio development challenging (40%), they also reported that it was effective for self-learning (54%). Differentiating between the concepts "reflection" and "evaluation" in CPD was problematic for some students and the use of clearer, simpler language should be used to explain these processes in future CPD work.